Cooperativismo agrícola no norte do Paraná : arranjos institucionais e seus impactos nas pequenas propriedades rurais - Rodrigues, Rosângela Mazzia Inocêncio (2016)
This thesis had as objective to verify the socioeconomic impact, experienced by the small agricultural properties associated, as a consequence of the new institutional arrangements embraced by the cooperative system of the North of Paraná. For the sustaining of the study, it was used as empirical reference the cooperative Cocamar Agribusiness (Cocamar Agroindustrial), based in the city of Maringá. It were adopted multiple sources of evidence, searching for conditions of the use of the triangulation techniques. The primary data were obtained upon semistructural interviews with 35 small producers cooperated. Their proprieties are located in nine cities of the Paraná, where operating units of the cooperative are located, as well as straight observation. The secondary data were collected upon analysis of the reports about agribusiness cooperativism and, particularly, about Cocamar, in addition to newsletters of the institutions involved with the agricultural sector. The handling of the data was carried out upon documental analysis and analysis of the subject matter for further foundation on the interviews conducted. The data indicate to a small capitalist producer, with properties with no more than 50 hectares and which perform basically with the products soybean, corn and orange. This producers dispose of the agricultural implements required to all productive process, employ temporary and / or constant labor, since the family doesn't act in the property, invest in production technology and carry out the rental of the farmland, seeking the increase of the productivity, demonstrating an accumulation of the capital received by the profit generated in the trade of the products. In the social context, the producers live in masonry houses, own vehicles and perform physical and social activities aiming the improvement of standard of living. Although there are divergence in their position regarding the cooperative role in the socioeconomic development of these members, most of them believe that they would have the same economic conditions if they weren't involved with the cooperative sector, once it offered, besides the improvement in the trade process, the technical assistance and access to new technologies that provide productivity development. The small producers state that the development of the cooperative happened with the development of the own member and that this meets all the social agents that are involved in the procedure (the government, employees, executives and agriculturists). Therefore, it is concluded that the arrangements used by the cooperative affected the socioeconomic development of its members.